TU1.3 A pilot survey of surgeons' knowledge regarding vagus nerve injury. (9th August 2022) - Dunstan, Matt; Kaur, Vasha; Bezzaa, Sabrina; Nehra, Dhiren
Abstract: Aims: Vagus nerve injuries occur in up to 42% of patients following anti-reflux operations. Vagal nerve injuries may have a significant impact on patients' quality of life after benign Upper GI hiatal surgery, and may go unrecognised. We aimed to explore surgeons' knowledge and practice regarding consenting, identifying the vagus nerve intraoperatively, and managing vagus nerve injuries. Methods: A pilot survey was distributed to General Surgical Trainees and Consultants in South East England via social media groups and Twitter. Respondents from other regions were permitted. Results: Nineteen respondents comprised 1 SHO, 14 Registrar grades/fellows and 4 Consultants. Seventy-four percent reported routinely discussing vagus nerve injury, of whom over 70% discussed symptoms of fullness and/or bloating, but only 36% discussed the need for further procedures. Eighteen respondents were involved in anti-reflux and paraoesophageal hernia procedures, of whom 94% routinely visualised the posterior vagus nerve during these procedures, whilst around 60% visualised the anterior vagus nerve. Ten respondents were involved in gastric band insertion, of whom 60% did not identify either vagus nerve. Only 7 respondents had experience of managing patients with vagus nerve injury. Conclusions: Work is required to guide education around informing patients of the risk of vagus nerve injury, and around managing this complication. This pilot survey informs wider national work to explore this topic.